Prevalence and Risk Factor Analysis of Bovine Trypanosoma Infection in Cattle across Three Egyptian Governorates - Selim, Abdelfattah; Marzok, Mohamed; Gattan, Hattan S.; Alruhaili, Mohammed H.; Ismail, Hesham; Hereba, Abdelrahman M. (Acta parasitologica, 2025)
A cross-sectional study was conducted in three governorates of the Nile Delta region in Egypt from January to December 2024. The objective was to determine the seroprevalence of bovine trypanosomosis and evaluate associated risk factors. A total of 540 cattle blood samples were examined using the CATT/ T. evansi test, and relevant animal data were analyzed to identify risk associations. The overall prevalence of trypanosomosis was 24.4% (132/540), with the highest rate observed in Kafr El-Sheikh governorate at 26.1% (49/188). The prevalence was significantly associated with age, packed cell volume (PCV), and body condition score ( P < 0.05). Multivariable logistic regression analysis showed that the likelihood of infection increased fourfold in cattle older than 3 years, twofold in anemic animals, and threefold in those with poor body condition. The findings indicate that bovine trypanosomosis is a prevalent among examined cattle in the area studied. Therefore, the implementation of strategic prevention and control programs is essential to improve livestock health and productivity.